Speech Prosody 2016 2016
DOI: 10.21437/speechprosody.2016-68
|View full text |Cite
|
Sign up to set email alerts
|

Cross-language data on five types of prosodic focus

Abstract: To examine the relative roles of language-specific and language-universal mechanisms in the production of prosodic focus, we compared production of five different types of focus by native speakers of English and Mandarin. Two comparable dialogues were constructed for each language, with the same words appearing in focused and unfocused position; 48 speakers recorded two dialogues each in their respective native language. Duration, F 0 (mean, maximum, range), and rmsintensity (mean, maximum) of all critical wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
3
5
0
Order By: Relevance
“…This acoustic finding is noteworthy in light of a recent production study [8] from our laboratory, where a greater degree of F 0 range expansion production of focused words was found for Mandarin speakers compared to English speakers. Given that salience is fundamentally gradient [22], it could be the case that Mandarin speakers start to expand their pitch range quite early in the utterance, in preparation for pitch range exaggeration on the focused word.…”
Section: Length Of Stay In Australia (Days)supporting
confidence: 61%
See 2 more Smart Citations
“…This acoustic finding is noteworthy in light of a recent production study [8] from our laboratory, where a greater degree of F 0 range expansion production of focused words was found for Mandarin speakers compared to English speakers. Given that salience is fundamentally gradient [22], it could be the case that Mandarin speakers start to expand their pitch range quite early in the utterance, in preparation for pitch range exaggeration on the focused word.…”
Section: Length Of Stay In Australia (Days)supporting
confidence: 61%
“…As demonstrated in previous production studies [8,19,21], prosody can be used for producing focused words in Mandarin in ways that do not interfere with tonal identity (e.g., by exaggeration of pitch register). However, what is interesting here is the perceptual reflection of this dual role for F 0 : Mandarin listeners could make use of the preceding intonation Target: [p h ] mei2 joʊ3 ɻən2 tsaɪ4 ʈʂʊŋ1 kɔ3 nəŋ2 ɕiɑŋ1 ɕin4 pʰu2 tʌ0 nəŋ2 ʈʂz 4 tsɑʊ4 ɕjɛn2 ʂweɪ3…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It is frequently used to signal given vs. new (Pierrehumbert and Hirschberg, 1990) and contrast (Liu, 2020). It is also commonly used to make corrections (Ip and Cutler, 2016) or help listeners to anticipate what the speaker is going to say (Levis and Levis, 2018).…”
Section: Pitchmentioning
confidence: 99%
“…They further concluded that Mandarin uses sentence stress to indicate discourse-level information and make contrasts. Analyzing five types of focus in Mandarin and English, Ip and Cutler (2016) found that Mandarin speakers showed greater increase in pitch range and pitch level for new-information focus.…”
Section: L2 Sentence Stressmentioning
confidence: 99%